Capital Mobility for Developing Countries May Not Be So High - Thomas D. Willett; Young Seok Ahn; Manfred W. Keil (Claremont McKenna College, Department of Economics, 2000)
International capital flows to developing countries have taken on considerable policy importance in recent years. There is disagreement, however, about whether financial capital mobility has become so high that developing countries have little ability to sterilize capital flows. This paper reviews several popular methods of estimating the degree of capital mobility for developing countries and shows that they are subject to potentially important upward biases due to inappropriate assumptions concerning the roles of domestic inflation and sterilization. Corrections for these factors can cut estimates of capital mobility by one half or more.
Keywords: F3; O1; G0; 330; sterilization; capital mobility; developing countries